Seroprevalence of Hepatitis C Virus among Health Care Workers - Uddin, MR; Islam, MMS; Hossain, MZ; Sarker, MN; Salimullah, ASM; Begum, F; Ahmed, DS; Alam, A; Roy, PK; Raihan, ASMA (Journal of Dhaka Medical College, 2010)
Context: Hepatitis C virus is one of the leading causes of liver disease and represents a major public health problem. It is a common cause of cirrhosis and hepatocellular carcinoma (HCC) as well as the most common reason for liver transplantation. Methods: A cross sectional study was carried out during the period of April 2007 to April 2008 among health care workers including phlebotomists, dialysis staffs and laboratory personnel handling blood and blood products. Total 200 health care workers from phlebotomists working at one stop collection centre of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka Medical College Hospital (DMCH), Dialysis staff working at haemodialysis units of BSMMU, Bangladesh Institute of Rehabilitation for Diabetes, Endocrine & Metabolic Diseases (BIRDEM), DMCH, National Institute of Kidney Diseases & Urology (NIKDU) had at least more than one year working exposure was enrolled in this study. After taking informed written consent detailed history was taken, clinical examination was done. 0.3 ml of venous blood was collected from each patient and tested for anti HCV by commercial kit, confirmed by ELISA method. Result: Among 200 patients majority (55.5%) of patients were below 30 years of age and there was equal prevalence among male and female. Out of 200 health care workers 1% was found to be anti HCV positive. All positive patient had duration of exposure of >5 years and had history of needle stick injury. Key words: Hepatitis C virus; seroprevalence; health care workers. DOI: 10.3329/jdmc.v18i1.6310 J Dhaka Med Coll. 2009; 18(1) : 70-74